Analisis Proses Pencatatan dan Pelaporan Transaksi Harian Teller pada KSP Kopdit Tuke Jung Cabang Utama - Blagin, Maria Sofiana; Herdi , Henrikus; Lamawitak, Paulus Libu (Jurnal Projemen UNIPA, 2026)
This internship report aims to analyze the process of recording and reporting daily teller transactions at the Savings and Loan Cooperative (Koperasi Simpan Pinjam/KSP) Kopdit Tuke Jung. The study focuses on the role of tellers in recording daily financial transactions and preparing transaction reports as the basis for the presentation of cooperative financial statements. The method used is a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation conducted during the internship period. The results of the analysis indicate that daily transaction recording at KSP Kopdit Tuke Jung has been carried out in a computerized manner using the Sikopdit application. Tellers record transactions based on transaction evidence, recap daily transactions, and prepare reports that are then submitted to the bookkeeping department and management. This process is in accordance with the accounting cycle theory, although there are still obstacles such as the potential for data input errors and system disruptions. Therefore, it is necessary to improve teller accuracy and optimize the accounting information system so that the process of recording and reporting daily transactions can run more effectively and accurately.